ANALISIS SISTEM PENGENDALIAN INTERN DALAM RANGKA MENJAGA ASET PERUSAHAAN DAN MENINGKATKAN EFEKTIVITAS PADA PT DHARMATAMA MEGAH FINANCE - Hj. Dewi Rejeki, SE., Ak., M.Ak. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
The purpose of this research is to know internal control system at PT Dharmatama Megah Finance in order to maintain company asset and improve the effectiveness of the company, related to the cause of branch offices that do not run SOP which has been set by head office at PT Dharmatama Megah Finance, Branch offices running SOPs that exist in PT Dharmatama Megah Finance. This research is a qualitative descriptive research where the data used is obtained from observation, interview/interview and documentation. Data analysis techniques used by assessing the internal control system that has been established headquarters based on the elements of internal control such as: Organizational Structure. Authority System and Recording Procedures, Healthy Practices and Employee Quality. Based on the results of research that has been done on PT Dharmatama Megah Finance, internal control system has not been all running properly. This is marked by the non-fulfillment of some elements of the internal control system that should be done branch companies. The cause of branch companies not running SOPs that have been established headquarters can be known after testing with 4 (four) elements of internal control as mentioned above, that the SOP has been established headquarters has not been obeyed by the branch office. In addition, the reliability of information from documents used also can not be accounted for